B2B Marketing in the Flexographic Machinery Industry - Verner, Jan; Tahal, Radek, 1970-; Petruška, Tomáš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
Soma Engineering, Czech engineering company, designed its new marketing strategy in order to succeed amongst its competitors in the flexographic machinery market. Goal of the thesis is to verify if the new marketing strategy of SOMA engineering leads to desired positioning of the company and its products in selected markets. In case, the research indicates that the strategy does not work, identify the areas/attributes where the company lacks behind the desired positioning. Desired positioning will be expressed by introducing set of quantifiable attributes and compared with values of the same set of attributes delivered by the marketing research of respective sales territories. As a conclusion, the company should be provided with the clear picture about its desired and real positioning in respective sales territories.
Vedoucí práce: Radek Tahal
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses